2015
DOI: 10.11648/j.ajls.20150304.18
|View full text |Cite
|
Sign up to set email alerts
|

Response of Potus Plants (Epipremnum Aureum) to Irrigation with Drainage Water of Ornamental Fish Basins and Magnesium Sulphate as Foliar Fertilizer

Abstract: This study was carried out at the laboratory of National Research Centre, Egypt during two successive seasons on 2012 and 2013 to study the response of potus plants ( Epipremnum Aureum) irrigated by drainage water of ornamental fish basins diluted with tap water (DWOFB) at the concentrations 100% DWOFB, 75% DWOFB + 25% Tap water and 50% DWOFB + 50% Tap water) and interacted with magnesium sulphate as foliar fertilizer rate (MFFR) at the concentrations MFFR1 (25 ppm) and MFFR2 (50 ppm). The results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Potus Plant (Epipremnum aureum) Metwally et al, (2015) laid out an experiment during two growing seasons 2012 and 2013 at the laboratory of National Research Centre, Egypt to determine the effect of potus plants (Epipremnum aureum) watered by waste water of attractive fish basins liquefy with tap water (DWOFB) at the levels 100% DWOFB, 75% DWOFB + 25% Tap water and 50% DWOFB + 50% Tap water) and combined with Epsom salt as foliar application level (EFAL) at the level EFAL1 (25 ppm) and EFAL (50 ppm). The results showed that the crop watered with total fish waste (100% fish) single or combined with magnesium 50 ppm achieved the maximum growth components, the maximum carbohydrate percentage enhanced in photosynthetic pigments.…”
Section: Garlic (Allium Sativum L)mentioning
confidence: 99%
“…Potus Plant (Epipremnum aureum) Metwally et al, (2015) laid out an experiment during two growing seasons 2012 and 2013 at the laboratory of National Research Centre, Egypt to determine the effect of potus plants (Epipremnum aureum) watered by waste water of attractive fish basins liquefy with tap water (DWOFB) at the levels 100% DWOFB, 75% DWOFB + 25% Tap water and 50% DWOFB + 50% Tap water) and combined with Epsom salt as foliar application level (EFAL) at the level EFAL1 (25 ppm) and EFAL (50 ppm). The results showed that the crop watered with total fish waste (100% fish) single or combined with magnesium 50 ppm achieved the maximum growth components, the maximum carbohydrate percentage enhanced in photosynthetic pigments.…”
Section: Garlic (Allium Sativum L)mentioning
confidence: 99%